Associations of preoperative hematocrit and platelet count with morbidity after pathologic fracture fixation - Mohyeddine El Sayed; Ryley Zastrow; Sassine Youssef; Adam S. Levin (Journal of Bone Oncology)
Background: Anemia and abnormal platelet count are common among patients with cancer and are associated with complications after orthopaedic procedures. We studied associations between these conditions and morbidity within 30 days after surgery for pathologic femur or humerus fracture. Methods: We retrospectively reviewed data from the National Surgery Quality Improvement Project database for 145,030 adults following surgical fixation of a pathologic femur or humerus fracture from 2010 to 2020. Multivariable logistic regressions compared 30-day complications between patients with mild or severe anemia versus those with normal hematocrit and between patients with thrombocytopenia or thrombocytosis versus those with normal platelet count. Results: Likelihood of extended hospitalization (≥6 days) was higher in patients with mild anemia (odds ratio [OR]: 1.47; 95 % confidence interval [CI]: 1.44, 1.51) and severe anemia (OR: 2.14; 95 % CI: 2.06, 2.23). Likelihood of all-cause morbidity was also higher among those with mild anemia (OR: 1.17; 95 % CI: 1.13, 1.21) and severe anemia (OR: 1.35; 95 % CI: 1.28, 1.42). Similarly, likelihood of extended hospitalization was higher in patients with thrombocytopenia (OR: 1.25; 95 % CI: 1.22, 1.29) and thrombocytosis (OR: 1.24; 95 % CI: 1.13, 1.36). Likelihood of all-cause morbidity was also higher for those with thrombocytopenia (OR: 1.12; 95 % CI: 1.07, 1.16) and thrombocytosis (OR: 1.21; 95 % CI: 1.07, 1.37). Conclusion: Preoperative anemia and platelet abnormalities were potentially modifiable risk factors associated with postoperative complications following surgery for pathologic fracture.